The effect of social influence mediated by attitude toward decision to purchase counterfeit luxury products - Agatha, Olivia; Irantha Hendrika Kenang (SEAN Institute, 2024)
The phenomenon of purchasing counterfeit luxury products is increasingly widespread among the public. Research related to purchasing decisions about counterfeit luxury products is very important and has an impact on a country's economy. Counterfeit luxury products are products that are sold to resemble genuine luxury goods but are sold at a much lower price. This can divert potential customers from the original shop, thereby causing a decrease in sales and income. The aim of this research was to determine the effect of social influence on the decision to purchase counterfeit luxury products which is mediated by attitude. This research is quantitative research. The population of this research is people who have purchased counterfeit luxury products. The sampling technique is convenience sampling. The number of respondents who participated in this research was 200 respondents. Data processing was carried out using Structural Equation Model analysis via the PLS application. The research results show that social influence and attitude partially influence the decision to purchase counterfeit luxury products. The results also found that social influence was able to provide a decision to purchase counterfeit luxury products which was mediated by attitude.